Effects of intellectual property rights on imitative ability, competitiveness and unemployment in developing countries - Mohamad, Asuantri (2020)
Essentially, the differences in the technology gap between developed and developing nations have led to various needs in protecting technology creation. Intellectual Property Rights (IPRs) protect technological innovation initiated from developed countries, while being imitated in the developing countries. Compliance to IPRs protection among World Trade Organisation (WTO) member countries, as stipulated in the agreement on Trade- Related Aspects of Intellectual Property Rights (TRIPS), seems to place pressure on the countries, particularly developing countries, as these countries heavily rely on the technology innovated from developed countries. In this study, three data sets are employed to achieve the three objectives. Specifically, the first objective of this study is to determine the impact of IPRs protection on imitative ability. Next, the second objective is to examine the role of IPRs protection in moderating the effects of FDI inflows on competitiveness, the third objective of this study is to investigate the relationship between IPRs protection and unemployment in the selected developing countries. The first objective of this study was achieved using the dataset derived from 2009 to 2014 among selected developing countries. For the second objective, dataset between 2008 and 2014 was utilised and 41 developing countries were selected. Lastly, the dataset between 2008 and 2014 was examined across 47 selected developing countries to meet the third objective. The system GMM estimator was applied for data analysis to achieve the outlined objectives of this study. This study draws several significant findings. First, IPRs protection does not weaken the imitative ability of the selected developing countries. The higher concentration of human capital accumulation, high FDI inflows and increase intervention from the government enhance imitative ability. Second, there is positive of moderating effect of IPRs protection on the relationship between FDI inflows and competitiveness in the selected developing countries. Third, stronger IPRs protection escalates unemployment in these countries, as evidenced by the positive relationship between the variables. The findings of this study aid policymakers to have better understanding of the relevance of maintaining IPRs protection in developing countries. Thus, in order to maintain a sustainable imitative ability, higher competitiveness and lower unemployment, the government should maintain an appropriate level of IPRs protection and encourage FDI inflows to developing countries. Since IPRs protection directly affects imitative ability, and consequently influences competitiveness as well as unemployment, these three factors should be appropriately managed in order to achieve high economic growth. It is recommended that further studies focus on the types of industries, so as to observe the effects of IPRs protection on these three factors.